Performance analyses on fluidized bed dryer integrated biomass furnace with and without air preheater for paddy drying - M yahya; Hendriwan Fahmi; Syafrul Hadi; Edison Edison (Institute of Advanced Engineering and Science, 2019)
The performance of a fluidized bed dryer integrated biomass furnace with air preheater (FBD with APH) and a fluidized bed dryer integrated biomass furnace without air preheater (FBD without APH) for drying of paddy have been evaluated. The FBD with APH and FBD without APH decreased the moisture of paddy from 24% (wet basis) to 14% (wet basis) within 43 and 47 minutes with average temperatures and relative humidities of 59.58 oC and 59.14oC, and 18.81% and 18.68%, respectively. The drying rate of paddy varied in the range of 0.11 kg/min-0.32 kg/min and 0.10 kg/min- 0.30 kg/min for FBD with APH and FBD without APH, with average values of 0.18kg/min and 0.17kg/min, respectively. The minimum, maximum, and average value speciﬁc moisture evaporation rate (SMER) was 0.20 kg/kWh, 0.57 kg/kWh, and 0.31 kg/kWh, respectively for FBD with APH, as well as 0.149 kg/kWh, 0.448 kg/kWh, and 0.252 kg/kWh, respectively, for FBD without APH. The specific energy consumption (SEC), the specific electrical energy consumption (SEEC), and the specific thermal energy consumption (STEC) were varied from 1.749 kWh/kg to 5.076 kWh/kg, 0.090 kWh/kg to 2.872 kWh/kg, and 0.760 kWh/kg to 2.204 kWh/kg, with average values of 3.528 kWh/kg, 1.96 kWh/kg, and 1.532 kWh/kg, respectively for FBD with APH, as well as from 2.234 kWh/kg to 6.702 kWh/kg, 1.056 kWh/kg to 3.167 kWh/kg, and 1.179 kWh/kg to 3.536 kWh/kg, with average values of 4.391 kWh/kg, 2.075 kWh/kg, and 2.316 kWh/kg, respectively, for FBD without APH. The thermal efﬁciencies of the FBD with APH and FBD without APH were varied between 12.4% and 37.93%, and 9.78% and 29.82%, resvectively, with average values of 20.78% and 16.61%. The thermal efficiency of FBD with APH was higher compared to FBD without APH.